2012
DOI: 10.4049/jimmunol.1102628
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Invariant NKT Cells Reduces Inflammation-Induced Preterm Delivery in Mice

Abstract: This study sought to determine whether invariant NKT (iNKT) cells play an essential role in inflammation-induced preterm delivery. Preterm delivery and fetal death rates were determined in wild-type (WT) C57BL/6 mice and iNKT cell-deficient Jα18−/− mice injected i.p. with LPS. The percentages of decidual immune cells, including activated subsets, and costimulatory molecule expression were analyzed by flow cytometry. Th1 and Th2 cytokine production in the culture supernatants of decidual mononuclear cells was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 42 publications
2
45
0
Order By: Relevance
“…136 The injection of LPS at 15 dpc caused preterm birth in wild-type mice but not in iNKT cell-deficient mice, 136 suggesting that iNKT cells modulate the process of labor induced by microbial products. Conversely, the stimulation of iNKT cells in vivo by injection of α-galactosylceramide during late gestation (16 dpc) induced early preterm birth (17 dpc), 128 which may be due to an expansion of NK1.1 + TCRαβ + NKT cells in the uterus.…”
Section: Bridges Between the Innate And Adaptive Immune Systems In Tementioning
confidence: 99%
“…136 The injection of LPS at 15 dpc caused preterm birth in wild-type mice but not in iNKT cell-deficient mice, 136 suggesting that iNKT cells modulate the process of labor induced by microbial products. Conversely, the stimulation of iNKT cells in vivo by injection of α-galactosylceramide during late gestation (16 dpc) induced early preterm birth (17 dpc), 128 which may be due to an expansion of NK1.1 + TCRαβ + NKT cells in the uterus.…”
Section: Bridges Between the Innate And Adaptive Immune Systems In Tementioning
confidence: 99%
“…For comparison of multiple variables, ANOVA was used. Differences were considered to be statistically significant when P!0.05 (Ilievski & Hirsch 2010, Li et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have attempted to study the etiopathogenesis of pregnancy failure, and microbial infection has emerged as an important cause of pregnancy failure in many of these studies. A large body of evidence indicates that inflammatory cytokines and chemokines are involved in bacterial and viral infections (Lin et al 2009a, Ilievski & Hirsch 2010, Li et al 2012. Further data highlighting the significant relationship between Toll-like receptors (TLRs) and adverse pregnancy outcomes have drawn considerable attention (Filipovich et al 2009, Lin et al 2009b,c, 2014, Sun et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been described that facilitate the isolation of infiltrating leukocytes from the murine tissues at the maternal-fetal interface throughout pregnancy 31,38,39,[43][44][45][46] . The protocol described herein offers a novel approach that combines the use of gentle mechanical and enzymatic tissue dissociation techniques to preserve the integrity of extracellular markers in the leukocytes isolated from the placenta and the decidual and uterine tissues of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the use of trypsin 32 , collagenase 37 , DNase 31 , dispase 38 , and commercial cocktails of various enzymes 32,39 . However, the nature and concentration of different enzymes and the duration of digestion must be meticulously defined and validated in order to ensure maintenance of the integrity of the cell surface antigenic epitopes required for immunophenotyping.…”
Section: Introductionmentioning
confidence: 99%